Takotsubo cardiomyopathy and coronary artery disease: value of cardiac magnetic resonance imaging for diagnostic confirmation: a case report. Issue 1 (22nd December 2018) - Díaz-Navarro, Rienzi; Villagran, Francisco
Abstract: Background: Takotsubo cardiomyopathy (TCM) is a reversible acute cardiac disease that mimics acute myocardial infarction (AMI). In patients with a history of an old myocardial infarction who develop TCM, cardiac magnetic resonance imaging (CMRI) is the first-line non-invasive diagnostic tool for clearly discriminating between AMI and TCM. Case summary: A 65-year-old woman who suffered a myocardial infarction in 2012, was admitted to undergo sigmoid colon tumour surgery in January 2017. Soon after surgery, she developed angina associated with ST-segment elevation, as shown by electrocardiography and increased cardiac enzyme levels. Acute coronary syndrome was diagnosed. She had a good clinical response to treatment with intravenous nitroglycerine, opioids, clopidogrel, aspirin, bisoprolol, and atorvastatin. Transthoracic echocardiography (TTE) showed anteroseptal and apical left ventricular akinesia with balloon-like dilatation, akinesia of the inferior wall and inferior interventricular septum, and global systolic dysfunction. Coronary angiography did not identify coronary artery lesions, and a tentative diagnosis of TCM was made. Cardiac magnetic resonance imaging confirmed the segmental contraction abnormalities seen in the TTE and identified myocardial oedema without delayed hyperenhancement after gadolinium administration, which confirmed the diagnosis of TCM and ruled out acute ischaemic damage. She was discharged when asymptomatic. Cardiac magnetic resonance imaging at 2 months showed disappearance of the anteroseptal and apical contraction abnormality, regression of myocardial oedema and normalization of global left ventricular systolic function. Discussion: This case confirms that CMRI is a non-invasive diagnostic method for accurately differentiating between AMI and TCM in patients with a prior myocardial infarction. cardiac magnetic resonance imaging should be incorporated as a diagnostic criterion for TCM.